Effectiveness of a FOUR Consciousness Assessment Workshop on Nurses’ Knowledge and Competence in Managing Head Trauma:A Pre-Experimental Study - Eva Yustilawati; Ardian Adhiwijaya; Ilhamsyah Ilhamsyah; A. Inda Fadhillah Ramadhani (Direktorat Politeknik Kesehatan Makassar, 2026)
Based on global epidemiological trends over the years, traumatic brain injury (TBI) remains one of the most common neurological disorders and continues to pose a substantial public health burden worldwide. The FOUR Scale, which is more comprehensive than the GCS because it evaluates brainstem reflexes and respiratory patterns and is applicable to both intubated and non-intubated patients, remains underutilized in several hospitals due to limited nurse knowledge and insufficient training, highlighting the need for structured educational interventions. This study aimed to evaluate the effectiveness of a FOUR Scale consciousness assessment workshop in improving nurses’ knowledge and competence in managing head trauma patients at RSUD Syech Yusuf, Gowa Regency. A quantitative approach using a pre-experimental one-group pretest–posttest design was applied, involving 40 nurses selected through total sampling. Data were collected using a validated and reliable knowledge questionnaire and competence observation sheet (Cronbach’s α 0.738) and analyzed using the Wilcoxon Signed Rank Test based on Z-scores, p-values, and effect sizes. The findings demonstrated a significant increase in knowledge (Z = –5.231; r = 0.827; p = 0.001) and competence (Z = –6.325; r = 0.99; p = 0.001) after the workshop. The large effect sizes indicate that the workshop had a strong positive impact on participants’ clinical abilities. These results confirm that training incorporating theoretical instruction, simulation, case discussions, and reflective learning can effectively enhance clinical competence. The FOUR Scale workshop proved effective and is recommended for routine implementation as part of emergency care quality improvement and as a component of hospital Standard Operating Procedures (SOPs)